2020
DOI: 10.1590/2179-8087-floram-2018-0004
|View full text |Cite
|
Sign up to set email alerts
|

Production of Joints Of Eucalyptus Sp. to Obtain Edge Glued Panels

Abstract: This research aimed at evaluating the quality of bonded joints of Eucalyptus wood by using different faces and adhesives to produce EGP (Edge Glued Panels). Glue line shear specimens were obtained from bonded joints glued with PVAc (Polyvinyl Acetate) and EPI (Emulsion Polymer Isocyanate) adhesives, using pieces oriented with tangential, radial and intermediary faces, as well as the combination between them. The specimens were submitted to two pretreatments in order to simulate the use of joints in dry and wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
(2 reference statements)
3
1
0
Order By: Relevance
“…Furthermore, it is observed that in the bonding process, for each species or mixed joints, the highest strength was associated with the use of the EPI adhesive. These results corroborate other studies that also found superiority for EPI adhesive compared to PVA (França et al 2020; Bila et al 2021).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, it is observed that in the bonding process, for each species or mixed joints, the highest strength was associated with the use of the EPI adhesive. These results corroborate other studies that also found superiority for EPI adhesive compared to PVA (França et al 2020; Bila et al 2021).…”
Section: Discussionsupporting
confidence: 92%
“…As for the adhesive factor, the results showed greater strength to shear stress when the side joints were bonded with EPI instead of PVA. This result was also found in the dry state in studies on bonded joints of wood from other species (França et al 2020; Bila et al 2021). This was probably due to the curing of the EPI adhesive occurring by the reaction of its isocyanate groups with the hydroxyl groups of the wood, promoting stronger chemical adhesion (França et al 2020).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…For Eucalyptus sp. using EPI adhesive at a spreading rate of 180 g.m -2 ,França et al (2020) found a shear resistance of 12.77 MPa in the dry condition and 8.84 MPa in the wet condition. WhileIwakiri et al (2021) using the same adhesive and spreading rates for E. Cariniana domestica, 5.23 MPa for Copaifera paupera, and 4.31 MPa for Cedrelinga cateniformis in wet pre-treatment, using the same adhesive and spreading rates as in the present study.…”
mentioning
confidence: 93%